2010
DOI: 10.1103/physrevb.82.121404
|View full text |Cite
|
Sign up to set email alerts
|

Mode-specific reactivity ofCH4onPt(110)(1

Abstract: The state-resolved reaction probability of CH 4 on Pt͑110͒-͑1 ϫ 2͒ was measured as a function of CH 4 translational energy for four vibrational eigenstates comprising different amounts of C-H stretch and bend excitation. Mode-specific reactivity is observed both between states from different polyads and between isoenergetic states belonging to the same polyad of CH 4 . For the stretch/bend combination states, the vibrational efficacy of reaction activation is observed to be higher than for either pure C-H stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…In a study of methane dissociation on Pt(110) 21 Bisson et al prepared CH 4 in four different vibrationally excited eigenstates and measured the state resolved reactivity for each of these states as well as the laser-off reactivity. The data were again analysed by fitting S-shape reactivity curves of the form given above with identical A(n i ) and W(n i ) values in order to determine the value of E n i 0 for each state and the results used to calculate the vibrational efficacies for the four different vibrational states shown in Table 1.…”
Section: This Journal Is © the Royal Society Of Chemistry 2016mentioning
confidence: 99%
“…In a study of methane dissociation on Pt(110) 21 Bisson et al prepared CH 4 in four different vibrationally excited eigenstates and measured the state resolved reactivity for each of these states as well as the laser-off reactivity. The data were again analysed by fitting S-shape reactivity curves of the form given above with identical A(n i ) and W(n i ) values in order to determine the value of E n i 0 for each state and the results used to calculate the vibrational efficacies for the four different vibrational states shown in Table 1.…”
Section: This Journal Is © the Royal Society Of Chemistry 2016mentioning
confidence: 99%
“…1 The emergence of quantum state-resolved experimental techniques using state-specific reactant preparation by laser excitation of the incident species has greatly increased the level of detail available from molecular beam experiments. [2][3][4] Stateresolved reactivity measurements have demonstrated both mode-specificity and bond-selectivity [5][6][7][8][9] as well as stereodynamical control 10 for chemisorption of methane on transition metal surfaces. Highly detailed data provided by state-resolved experiments enable stringent tests of ab initio theory of gas/surface reaction dynamics, 11,12 helping experimentalists and theorists to work towards the ultimate goal of using computers to predict surface reactivity with chemical accuracy in order to design and optimize heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed quantum state resolved reactivity studies of collisions at the gassurface interface have illustrated the additional information that can be obtained through such initial state preparation, by revealing the influence of the ro-vibrational state of the molecule on the outcome of the collision. [1][2][3][4] For example, it has been shown that the chemisorption of methane on transition metal surfaces is both bond 5,6 and mode 7,8 specific, as well as being dependent on the alignment of the impinging molecule. 9 In order to realize such quantum state resolved reactivity measurements, a significant fraction of the reactant molecules needs to be prepared in a specific ro-vibrational eigenstate.…”
Section: Introductionmentioning
confidence: 99%